Fiber and free-space practical decoy state QKD for both BB84 and SARG04 protocols - Ali, Sellami; Wahiddin, Mohamed Ridza (EDP Sciences, Società Italiana di Fisica and Springer-Verlag, 2010)
Fiber and free-space practical decoy state quantum key distribution has been simulated for both BB84 and SARG04 protocols. The numerical simulation has shown that the fiber based QKD and free space QKD systems using the proposed method for BB84 are able to achieve both a higher secret key rate and greater secure distance than that of SARG04